Evaluation of extensions of luxury brands:the case of fragrances in Portugal - Figueiredo, José António (2016)
Fragrances are part of the market of personal luxury goods, which represents the second most important segment of the luxury industry. Luxury brands have been implementing new marketing strategies, such as the use of brand extensions. This strategy has become fundamental to the business model of many luxury brand. This research has the intention to understand the influences that have determined the consumption of fragrances, inferring about the symbolic meaning of its purchase. Additionally, it tries to evaluate whether fragrances are a success, as an extension of a luxury brand. This study adopts a qualitative approach in the form of in-depth interviews with consumers of fragrances. Findings indicate that fragrances are a fundamental product, used in a daily basis, which shows some distinctive personal characteristics from their consumers. Additionally, fragrances used as an extension of a luxury brand are seen as a success, especially to the brand.